2003
DOI: 10.1242/dev.00847
|View full text |Cite
|
Sign up to set email alerts
|

Morpholino-based gene knockdown screen of novel genes with developmental function inCiona intestinalis

Abstract: In the present study, we conducted an extensive analysis to identify novel genes with developmental function among Ciona intestinalis genes discovered by cDNA projects. Translation of a total of 200 genes expressed during embryogenesis was suppressed by using specific morpholino antisense oligonucleotides. Suppression of the translation of any of 40 genes (one-fifth of the genes tested) was thereby shown to cause specific embryonic defects. Most of these genes have counterpart(s) in mouse and human, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 60 publications
5
78
0
Order By: Relevance
“…1C). The fact that the mutant 411 phenotype is similar to previous reports for Ciona embryos with downregulated or knocked-down brachyury (Di Gregorio et al, 2002;Satou et al, 2001;Yamada et al, 2003) allowed us to confidently conclude that the mutant phenotype was due to a loss-of-function brachyury allele. In addition, we observed that four genes previously shown to be downstream of brachyury [noto4, noto8, prickle (pk) and tropomyosin (Hotta et al, 2000)] and laminin alpha 3/4/5 were not expressed in homozygous mutant 411 embryos (data not shown).…”
Section: Results and Discussion Isolation Of An Enu-induced Ciona Intsupporting
confidence: 83%
See 2 more Smart Citations
“…1C). The fact that the mutant 411 phenotype is similar to previous reports for Ciona embryos with downregulated or knocked-down brachyury (Di Gregorio et al, 2002;Satou et al, 2001;Yamada et al, 2003) allowed us to confidently conclude that the mutant phenotype was due to a loss-of-function brachyury allele. In addition, we observed that four genes previously shown to be downstream of brachyury [noto4, noto8, prickle (pk) and tropomyosin (Hotta et al, 2000)] and laminin alpha 3/4/5 were not expressed in homozygous mutant 411 embryos (data not shown).…”
Section: Results and Discussion Isolation Of An Enu-induced Ciona Intsupporting
confidence: 83%
“…The structure and function of brachyury has been extensively characterized in a number of chordates, including the ascidian (Satoh, 2003;Showell et al, 2004). In ascidians, brachyury is expressed in the notochord precursor and the notochord (Corbo et al, 1997;Imai et al, 2000;Yasuo and Satoh, 1993), and experimental manipulations have confirmed its role in notochord development (Di Gregorio et al, 2002;Satou et al, 2001;Yamada et al, 2003;Yasuo and Satoh, 1998). Both the molecular pathway inducing brachyury expression in the ascidian notochord precursor, and direct and indirect downstream targets of brachyury have been well characterized (Hotta et al, 2000;Hotta et al, 2008;Imai et al, 2006;Nishida, 2005;Takahashi et al, 1999;Yagi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MO antisense sequence was TAGTACGGCGAGACATTTTAACTGG, and the control MO sequence with five nucleotide mismatches was TAcTAgGGCGAcAgATTTTAACTcG. On the basis of previous studies, 10 fmoles MO in distilled water was injected into intact fertilized eggs (75).…”
Section: Mo Injectionmentioning
confidence: 99%
“…Fertilized wild-type eggs were injected the dmrt-MO or control-MO, 5Ј-CCTCTTACCTCAGTTACAATTTATA-3Ј, as described (Yamada et al, 2003).…”
Section: Savignyi Geneticsmentioning
confidence: 99%